Influence of Cinnamon Extract (Cinnamomum burmanii) Provision on the Reduction of Blood Glucose Level of Hyperglycemic Male Wistar Rats - Aulia, Kharina; Wirjatmadi, Bambang; Adriani, Merryana (Health Notions, 2018)
The number of patients with hyperglycemia in the world and in Indonesia is estimated to increase rapidly in the next 25 years. The content of cinnamaldehyde, flavonoids, polyphenols, and chromium in cinnamon thought to have an influence of hypoglycemia. This study aimed to determine the influence of cinnamon extract to a decrease of blood glucose levels in hyperglycemic rats induced by a single dose of alloxan as much as 125 mg/kg. This study was laboratory experiment by using RAL (Complete Randomize Design) with Pre-Post Test Control Group Design Research. Experimental animals used were male Wistar rats divided into 5 groups. KN was negative control group. KP was hyperglycemic positive control group. P1 was the first treatment group (a dose of 200 mg/kg). P2 was the second treatment group (a dose of 250 mg/kg). P3 was the third treatment group (a dose of 300 mg/kg). Cinnamon therapy was given orally for 14 days. The results of this research was tested statistically by using One Way ANOVA and showed that there were significant differences between the blood glucose levels in the treatment group with the positive and negative control groups. The conclusion was that the provision of cinnamon extract for 14 days could provide an influence of lowering blood glucose levels.  Keywords: Blood glucose, Cinnamon, Hyperglicemia